Optimization of dye adsorption capacity and mechanical strength of chitosan aerogels through crosslinking strategy and graphene oxide addition. (1st May 2019) - Salzano de Luna, M.; Ascione, C.; Santillo, C.; Verdolotti, L.; Lavorgna, M.; Buonocore, G.G.; Castaldo, R.; Filippone, G.; Xia, H.; Ambrosio, L.
Graphical abstract: Highlights: CS and CS/GO aerogels are prepared by crosslinking before or after freeze-drying. Crosslinking after freeze-drying improves the dye removal ability of CS aerogels. GO addition significantly improves the mechanical properties. GO addition also provides a high uptake capacity towards cationic dyes. The crosslinking strategy is crucial to optimize the properties of CS/GO aerogels. Abstract: Chitosan (CS) aerogels were prepared by freeze-drying as potential adsorbents for water purification, and the effect of the strategy of crosslinking was investigated by varying the amount of crosslinker (glutaraldehyde) and the sequence of steps for the preparation of the aerogel. Two procedures were compared, in which the crosslinking step was carried out before or after the freeze-drying of the starting CS solution. When crosslinking was postponed after the freeze-drying step, the adsorption capacity towards an anionic dye, such as indigo carmine, considerably increased (up to +45%), reaching values as high as 534.4 ± 30.5 mg g −1 . The same crosslinking strategy ensured a comparable improvement also in nanocomposite aerogels containing graphene oxide (GO), which was added to enhance the mechanical strength and provide adsorption capacity towards cationic dyes. Besides possessing good mechanical strength (compressive modulus higher than 1 MPa), the CS/GO aerogels were able to bind also cationic pollutants such as methylene blue. The maximum uptake capacity increased from 4.3 ± 1.6 to 168.6 ± 9.6 mg of cationic dye adsorbed per gram of adsorbent with respect to pristine CS aerogels.